Estimation of post-mortem interval based on insect species present on a corpse found in a suitcase. (January 2020) - Hu, Guoliang; Wang, Man; Wang, Yu; Liao, Mingqing; Hu, Jiayu; Zhang, Yingna; Yu, Yiming; Wang, Jiangfeng
Highlights: PMI determination based on insects of a body concealed in suitcase. Insects could colonize corpses in suitcase. Absence of certain species of insects could provide special clue for the case. Abstract: Murderers sometimes dispose of bodies in zipped suitcases in an attempt to conceal their crimes. In these cases, the species of insects found and their succession patterns are typically different from those found on exposed corpses due to hindrances or delays in colonization. Here we report a case in which an unidentified female corpse was found in a soft-shell suitcase in a wetland area among some reeds in Guangdong, China on 13 May 2018. The suitcase was unbroken and zippers were well-sealed. The victim was a young woman, naked, and curled up in the suitcase. The insect evidence we collected include (i) pupae and empty puparia of Chrysomya nigripes (Aubertin) (Diptera: Calliphoridae) and Fannia canicularis (Linnaeus) (Diptera, Muscidae), (ii) larvae, pupae and empty puparia of Megaselia scalaris (Loew) (Diptera: Phoridae) and Hermetia illucens (Linnaeus) (Diptera: Stratiomyidae). According to this insect evidence, we estimated the PMImin as 56 days. Bhadra et al. (2014) show that larvae of Calliphora vomitoria (Linnaeus) (Diptera: Calliphoridae) and Calliphora vicina (Robineau-Desvoidy) (Diptera, Calliphoridae) can colonize carcasses concealed in zipped suitcases. Although the size of the zipper (7 mm) in this case is larger than that described in Bhadra et al. (4 mm), we did not find Chrysomya megacephala (Fabricius) (Diptera: Calliphoridae), Chrysomya rufifacies (Macquart) (Diptera: Calliphoridae), or Lucilia sericata (Meigen) (Diptera: Calliphoridae) which usually colonize fresh corpses in this area. Therefore, we deduced that the victim may have been killed in winter. After the crime was solved, the murderer confessed that he killed the victim on 5 January.